Composition and conditions of sedimentation of the Osipa and the Chaidakh Formations (Upper Triassic) in the Pronchishev Range region (Middle Siberia) - A. Yu. Popov; E. S. Sobolev; A. V. Yadrenkin (Известия высших учебных заведений: Геология и разведка, 2015)
The new data on a composition of the Osipa and the Chaidakh Formations (Upper Triassic) in the Pronchishev Range region has been obtained. Stratigraphic subdivision of the geological succession by complex bio- and lithostratigraphic methods was carried. By results of the carried-out (implemented, done) litofaciesanalysis the studied deposits have been found to represent the uniform regressive sedimentological cycle with the transgressive pack in the basis. Consecutive change of sea-shallow sedimentation conditions by coastal is noted. The comparative analysis of the studied geological succession with basic successions of adjacent areas showed that its structure has the Leno-Olenek type but with moredistinct far-coastal deposits characteristics.